Thrips Species Composition on Grapes in Karnataka and Maharashtra - Ranganath, H R; Krishna Kumar, N K; Kumar, Vikas (Journal of Horticultural Sciences, 2008)
A survey was undertaken to document species composition of thrips on grape foliage, inflorescence and different stages of berry development such as mustard size (2 mm), sorghum size (4 mm), pea size (8 mm) and beyond pea size (> 8 mm) berries at Bijapur in Karnataka and Sangli in Maharashtra during January 2005 to January 2006. Cultivars sampled were Thomson Seedless, Sonaka, Sharad Seedless, Tas-A-Ganesh, 2A and B5 clones of Thomson seedless. Scirtothrips dorsalis Hood constituted over 90% of total thrips sampled from new flushes, inflorescence and berries in different stages during January, February, March and December 2005 at Bijapur followed by Thrips palmi Karny (1- 4.3%); Thrips hawaiiensis (Morgan) a hitherto unknown thrips species on grape dominated inflorescence (98.0%) on cv. Sonaka during December 2005 in the same area. Similar trend was observed in the vineyards of Sangli. Number of thrips, which was more on inflorescence declined as the berry matured. Least number of thrips was observed on berries > pea size. As recorded in Bijapur, T. hawaiiensis was dominant species on inflorescence of 2A (98.6%) and B5 (99.4%) clones of Thompson seedless. In other cultivars S. dorsalis was dominant that formed 92.8 -100% of total thrips collected. Thrips palmi constituted 0.8-1.7% of thrips collected from different parts of grape vine. Other unidentified thrips constituted 0.9-7.2%.
Keywords: Inflorescence; Scirtothrips dorsalis; Thrips hawaiiensis; Grapevine